An Inequality of Meromorphic Vector Functions and Its Application - Wu Zhaojun; Chen Yuxian (Abstract and Applied Analysis)
Firstly, an inequality for vector-valued meromorphic functions is established which extend a corresponding inequality of Milloux for meromorphic scalar-valued function (1946). As an application, the relationship between the characteristic function of a vector-valued meromorphic function f and its derivative f' is studied, results are obtained to extend some related results for meromorphic scalar-valued function of Weitsman (1969) and Singh and Gopalakrishna (1971).